THE ROLE OF CRYOSURGICAL SURGICAL MEASURES DURING ALVEOLAR LIVER DISEASE REOPERATIONS - B. I. Alperovich; N. V. Merzlikin; V. N. Salo (Креативная хирургия и онкология, 2017)
The  results  of  treatment of  36  reoperated patients suffering from   alveolar  liver disease  are analyzed  in the article. The patients were operated according to the know-how offered by one of the work writers.  Surgery results and late fate are considered. Palliative liver resections during  reoperations with cryodestruction of the  parasitic  tissue  part  make palliative surgery relatively radical.